Beyond the Jornadas de Junho: from the street demonstrations to the voice of the multitude – reflections on political exercises in public spaces in the era of networks | Por trás das Jornadas de Junho: das manifestações de rua à voz da multidão – reflexões sobre o exercício político nos espaços públicos em tempos de rede - Baptista, Piero Carapiá Lima; Espinoza, José Carlos Huapaya (Revista Brasileira de Estudos Urbanos e Regionais, 2016)
The month of June 2013 has entered the annals of recent Brazilian history, due to the street protests throughout the country’s major cities, which showcased facets of the country’s reality to a world already focused on Brazil, as it prepared to host the 2014 World Cup. The aim of this article is to summarize the manifestations, which took place in public spaces, contextualize them into recent Brazilian events, and demonstrate how they appeared as a consequence of the increasing loss of political voice in contemporary society due to globalization. This same phenomenon would seem to present its own possible solutions to the very problems it has created, such as those indicated by Milton Santos (2000), Hardt and Negri (2005), mostly through networked actions and the concept of “multitude”. However, having moved on a few years from the Jornadas de Junho, the particular dissensions and lack of clarity surrounding the demands reveal a horizon on which political participation is still vacillating and confused.